Platform Merdeka Mengajar (PMM): Transformation of Strengthening Principal Supervision in Teacher Work Effectiveness and Achievement Motivation - Iis Nurasiah; Din Azwar Uswatun; Deden Sumiarsaf; Umi Kalsom Takrif (Universitas Pendidikan Ganesha, 2024)
Problems related to teacher work effectiveness and achievement motivation remain a persistent challenge in the field of education, especially given the crucial role of school principals in conducting supervision. The optimal performance of both teachers and school principals serves as one of the key indicators of successful educational policy implementation. This study aims to analyze the influence of the Merdeka Mengajar Platform (PMM) in strengthening school principal supervision on teacher work effectiveness, and its correlation with teacher self-efficacy. A quantitative approach was employed using a survey method. The sample consisted of 106 teachers selected from a total population of 150, determined using the Slovin formula with a 5% margin of error. The research instrument was a questionnaire, with data analyzed through descriptive and inferential statistics. The results revealed three main findings: (1) there is a positive and significant relationship between principal supervision through PMM and teacher work effectiveness (r = 0.565); (2) there is a positive and significant relationship between self-efficacy and teacher work effectiveness (r = 0.595); and (3) there is a positive and significant joint relationship between principal supervision and teacher self-efficacy with teacher work effectiveness (r = 0.680). These findings suggest that the integration of digital platforms into supervisory practices can serve as an effective strategy to enhance teacher performance, particularly when supported by strong self-efficacy.